Optimizing Local Food through Brownie-Based Innovation Salak Fruit as a Functional Food to Prevent Stunting in Children - Keumala, Mayshinta Hasna; Adila, Martyana Ayu; Wijaksono, Wisnu Ari; Al Fakhri, Naufal; Putri, Wulan Dita; Fauzia, Syafamila; Khisan, Hindun Asvi Khaerotul; Sari, Anggraeni Kartika; Pradeka, Yunif Putra; Rakhmadani, Airin; Kartika, Ika; Tristanto, Andita Ari; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Stunting remains a complex public health challenge in Indonesia, especially in rural areas with limited access to nutritious food and low nutrition literacy. This study aims to identify and maximize local potential in stunting prevention efforts through the development of innovative food products made from salak. The method used was descriptive qualitative with a community-based participatory research (CBPR) approach, which involved various parties such as mothers of toddlers, Posyandu cadres, farmer women's groups, and community leaders in Pucungwetan Village, Sukoharjo District, Wonosobo Regency. The results of the activity showed that the training in making salak brownies was able to increase community understanding of the importance of nutritious local food consumption, as well as foster an entrepreneurial spirit that can support family economic independence. Apart from being an alternative to processed local food, this innovation also contributes to meeting the nutritional needs of children and pregnant women, so it has the potential to become a sustainable intervention in stunting prevention.